MULTIPLE INTELLIGENCE ACTIVITIES IN TEACHING ENGLISH FOR YOUNG LEARNERS - Tsurayya, Hana (2013)
This paper entitled "Multiple Intelligence Activities in Teaching English for Young Learners" was aimed to discover the multiple intelligence activities implemented by the teacher in teaching English for young learners and to reveal the students' responses toward Multiple Intelligence activities. This study is a descriptive qualitative study involving an English teacher who taught kindergarten students as the respondent. The obtained data were analyzed by using Armstrong's framework (2009) of Multiple Intelligence Activities. The data collection methods used observation, interview, and data analysis. The findings revealed that the teacher implemented eleven multiple intelligence activities in the classroom, namely drilling for linguistic; riddle and counting number in sequence for logic-mathematic; showing pictures and color games for spatial; body answer and take the ball game for bodily-kinesthetic; sing a song for musical; pairs game for interpersonal; personal connection for intrapersonal; and observe the weather for natural. The students' responses toward Multiple Intelligence activities are generally positive. The indicators of students' response can be observed from four aspects, namely: students' participation, students' achievement, students' potentials improvement, and students' way of learning. The results indicate that varieties of activity have been provided to accommodate students' interest and intelligences. However, those activities are not intended to cater each student's interests specifically. In conclusion, the implementation of Multiple Intelligence activities as has been observed in this study is an example of good practice as an attempt to providing learning experiences suited to the students' interests and intelligences. Keywords: young learners, multiple intelligences, activities, teaching English